Pengukuran Ketajaman Ground Sampling Distance (GSD) Di Berbagai Ketinggian Lahan Sawah Dengan Menggunakan Drone Tipe Mavic 2 Pro Di Desa Matani Kecamatan Tumpaan - Lamia, Franly J.I.; Rogi, Johannes E.X.; Tiwow, Diane (AGRI-SOSIOEKONOMI, 2023)
Drones are a solution for getting data efficiently and effectively. The drone is also equipped with a flight control system through waves, ground positioning system (GPS) precision navigation, and flight control electronics so that it can fly according to the autopilot flight plan. The purpose of this study was to measure the sharpness of the Ground Sampling Distance (GSD) at various heights of paddy fields using the MAVIC 2 PRO TYPE Drone in Matani Village, Tumpaan District. The results of the research on measuring the acuity of the Ground Sampling Distance (GSD) in paddy fields using the MAVIC 2 PRO TYPE Drone in Matani Village, Tumpaan District show that flying altitude affects GSD results where the higher the drone altitude, the greater the GSD value and the lower the altitude. fly, the clearer the photos obtained. It is better to measure the sharpness of the Ground Sampling Distance (GSD) in the afternoon above 9 am because the sun's lighting affects the quality of the photo at a height of 200 meters so that the photo is clear.